Characteristics Of Pathomorphological Changes In The Heart In Cases Of Sudden Cardiac Death (Texas Journal of Multidisciplinary Studies, 2023)
in the study, the morphometric changes of the heart of 100 people who died in 2018-2020 in the age range of 30-70 years who were observed cases of sudden cardiac death were studied macroscopically and microscopically. Atherosclerotic changes in coronary vessels, age-related changes in ischemia in sympathetic nerve bundles and myocardium, ventricular fibrillation and asystole, myocarditis, dilated and hypertrophic cardiomyopathies, pulmonary hypertension were studied in autopsy examinations of patients with sudden cardiac death